ChemInform Abstract: 2‐Bromo‐6‐isocyanopyridine as a Universal Convertible Isocyanide for Multicomponent Chemistry. Issue 29 (June 2016) - van der Heijden, Gydo; Jong, J. A. W.; Ruijter, Eelco; Orru, Romano V. A.
Abstract: The title pyridine is utilized in Ugi type and Passerini type reactions leading to various carboxylic amides.